2021
DOI: 10.3390/computers10040048
|View full text |Cite
|
Sign up to set email alerts
|

iSTART StairStepper—Using Comprehension Strategy Training to Game the Test

Abstract: Literacy skills are critical for future success, yet over 60% of high school seniors lack proficient reading skills according to standardized tests. The focus on high stakes, standardized test performance may lead educators to “teach-to-the-test” rather than supporting transferable comprehension strategies that students need. StairStepper can fill this gap by blending necessary test prep and reading comprehension strategy practice in a fun, game-based environment. StairStepper is an adaptive literacy skill tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…Crippen and Earl [28] developed a web-based learning tool that engages students in an environment that supports structured problem-solving. Although self-explanation has been shown to have a unique learning effect, it faces multiple barriers, including the resource-intensive nature of providing feedback on unstructured tasks, the lack of opportunities for students to practice self-explanation writing support, and the tendency for students to disengage from self-explanation activities before mastering self-explanation description skills [11]. To address these challenges, various methods have been proposed for processing self-explanation.…”
Section: Utilization Of Self-explanationmentioning
confidence: 99%
See 3 more Smart Citations
“…Crippen and Earl [28] developed a web-based learning tool that engages students in an environment that supports structured problem-solving. Although self-explanation has been shown to have a unique learning effect, it faces multiple barriers, including the resource-intensive nature of providing feedback on unstructured tasks, the lack of opportunities for students to practice self-explanation writing support, and the tendency for students to disengage from self-explanation activities before mastering self-explanation description skills [11]. To address these challenges, various methods have been proposed for processing self-explanation.…”
Section: Utilization Of Self-explanationmentioning
confidence: 99%
“…In previous research, instructors and researchers have often employed scripts to facilitate the selfexplanation task by manually creating prompts, paper-based exercises and templates, and feedback [3], including scaffold templates based on sample sentences [8][9][10]. However, it has also been suggested that research into computer-generated prompts and feedback could improve the scalability of self-explanation while ensuring consistency in the quality of the support that is required [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arner, McCarthy and McNamara [6] present StairStepper, an adaptive literacy skill training game within an Interactive Strategy Training for Active Reading and Thinking (iSTART) intelligent tutoring system. StairStepper models text passages and multiplechoice questions of high-stakes assessments, iteratively supporting skill acquisition through self-explanation prompts and scaffolding, adaptive feedback based on performance, and self-explanations.…”
mentioning
confidence: 99%